Insight into the impact of nanovoids on the electrical and mechanical properties of nanotwinned copper films. (August 2017) - Hu, Z.Y.; Du, J.L.; Wang, P.P.; Wang, X.J.; Zhang, Y.; Qiu, Y.H.; Fu, E.G.
Abstract: This article reports the impact of nanovoids on macro-properties and its underlying physical mechanism in nanotwinned Cu films with nanovoids synthesized via magnetron sputtering. The results indicate the resistivity due to nanovoids is proportional to void porosity at 4 K and the film hardness induced by nanovoids is proportional to void density in the slip plane while independent of void sizes. The ratio of hardness to resistivity is thus able to be improved by tuning nanovoids based on above findings. These findings will definitely provide references for the future study on the improvement of materials' properties synthesized by sputtering deposition techniques. Graphical abstract: